Application of intermittent warming to enhance postharvest quality and extend the shelf life of pomegranate fruit (Punica granatum). Issue 6 (19th September 2022) - Fawole, Olaniyi Amos; Yanclo, Loriane Jennifer Ayo-ola; Opara, Umezuruike Linus
Abstract : Intermittent warming (IW) cycles slow down the physiology of fresh horticultural commodities, thereby extending their storage life. We investigated the effects of IW on physiological disorders, physicochemical, sensory parameters and the emission of volatile organic compounds (VOCs) of pomegranate ( Punica granatum ; cv. Wonderful) fruit during a 3-month cold storage period. Pomegranate fruit batches were subjected to IW cycles of 3d at 5°C, followed by 1 d at 20°C (IW 3d) and 6 d at 5°C, followed by 1 d at 20°C (IW 6d). During cold storage at 5°C, fruit samples were transferred to shelf-life conditions at 20°C for 4 d before analysis was performed monthly. Continuous fruit mass loss was observed across all treatments during storage but was highest ( p  < 0.05) for untreated samples at the end of this study. Fruit decay was minimized by 15% and 16% for IW 3d and IW 6d, respectively, compared to 42% for the control. In contrast, a higher incidence of chilling injury was observed in the treated fruits than in control. Therefore, IW 3 d at 5°C is recommended for decay reduction in pomegranate fruit (cv. Wonderful) and shelf-life extension for up to 3 months of storage.